Short- and long-run linkages between employment growth, inflation and output growth: evidence from a large panel - Škare, Marinko; Caporale, Guglielmo Maria (Technological and Economic Development of Economy, 2014)
This study examines the short- and long-run linkages between employment growth, inflation and output growth applying panel cointegration and causality tests to data for 119 countries over the period 1970–2010. We find evidence of positive Granger causality running from output growth to employment growth in the short run. Employment growth Granger causes output growth with a negative sign in the long run. Inflation Granger causes employment and output growth positively in the short run and negatively in the long run.